ОБЗОР И РАЗРАБОТКА ПРОГРАММЫ ПО СБОРУ ЭЛЕКТРОННЫХ РЕСУРСОВ НА КАЗАХСКОМ ЯЗЫКЕ ПО ЗАКОНОДАТЕЛЬСТВУ РЕСПУБЛИКИ КАЗАХСТАН («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The work is devoted to the development of a program for collecting electronic resources. With the rapid digitalization of teaching media, cultural archives and communications, the issue of effective collection, storage and use of language data becomes key to the preservation of cultural heritage and the maintenance of linguistic diversity. The study conducted a literature review covering relevant aspects of electronic resources, language data and data collection programs. The goal of the work is to develop a program specific to the Kazakh language. In the process of research, the tasks of studying the legislative framework, analyzing existing programs and developing a universal data collection system in the Kazakh language are solved.
Keywords: electronic resources, Kazakh language, crawling.